MARKET REACTION TO MERGER ANNOUNCEMENT: EMPIRICAL STUDY ON THE COMPANIES LISTED ON IDX (INDONESIA STOCK EXCHANGE) - B11111044, BETI SEPLIANTINI (Jurnal Manajemen Update, 2015)
The aim of the research was to reveal the reaction of the stock market on the company to merger announcements. It was an empirical study on the companies listed on IDX (Indonesia Stock Exchange) in the period 2004-2014 by looking at the abnormal return around the time of the announcement, comparing the average abnormal return and the average trading volume activity before and after the merger. This was a comparative research a case study. It was also an event study. The population in this study included 39 companies that announced merger in the period of 2004-2014 with a total sample of 30 companies selected through a purposive sampling technique. The period of the research was 21 days, 10 days before and 10 days after the announcement.   The results of the research showed that the probability value or significance value of AR, AAR and TVA was greater that the significance level used. The abnorrnal return around   the   time   of   the   announcement   was   not   significant   either   before   the announcement t-10 until t-1 or after the announcement t+1 until to t+10, and at the time of the announcement t+0. The average abnormal return (AAR) 10 days before and 10 days after the announcement was 0.899>0.05 meaninng there was no significant difference before and after the merger announcement. The average TVA 10 before and 10 days after the announcement was 0.600>0.05 so there was no significant difference. It can be concluded that the average AR and the average TVA before and after the announcement of the merger indicated that there was no significant difference.   Keywords: Merger Announcement, Event Study, Abnormal Return, Trading Volume Activity.